Predictors of Falls in Patients with Degenerative Cervical Myelopathy: A Prospective Multi-institutional Study. Issue 15 (1st August 2021) - Inose, Hiroyuki; Yoshii, Toshitaka; Kimura, Atsushi; Takeshita, Katsushi; Inoue, Hirokazu; Maekawa, Asato; Endo, Kenji; Miyamoto, Takuya; Furuya, Takeo; Nakamura, Akira; Mori, Kanji; Kanbara, Shunsuke; et al.
Abstract : Study Design: Prospective multicenter study. Objectives: The purpose of this study was to characterize a population of patients with degenerative cervical myelopathy (DCM) combined with a history of falling, and to identify the predictors associated with those falls. Summary of Background Data: Falls among patients with DCM are common and can lead to the worsening of neurological symptoms. However, there are no prospective studies that have investigated the risk factors for falls in these patients. Methods: We prospectively enrolled patients scheduled for surgery for DCM and evaluated the significance of various preoperative measures for predicting falls. We then examined the correlation between the number of falls and the preoperative factors. Lastly, we performed stepwise logistic regression analysis to assess the concurrent effects of various factors on the occurrence of falls. Results: Among the 135 patients analyzed, 64 experienced one or more falls from the time of enrollment to 1 year postoperatively. Univariate analysis showed that the preoperative potassium and albumin levels, handgrip strength, and the Japanese Orthopaedic Association score for the assessment of cervical myelopathy (C-JOA score) were lower and Nurick grade was higher in the fallers group. Serum potassium level, handgrip strength, C-JOA score, Nurick grade, European Quality of Life-5 Dimensions (EQ-5D) score, t1 pelvic angle, and sagittal vertical axis had weak correlations with the number of falls. The fallers group had a lower C-JOA and EQ-5D scores and a lower recovery rate at one year postoperatively. Stepwise multiple logistic regression analysis identified preoperative potassium level and handgrip strength as the independent preoperative predictors for falling. Conclusion: We identified preoperative lower serum potassium level and weaker handgrip strength as significant predictors of falls in patients with DCM. Therefore, DCM patients with these risk factors should be cautious about falls and might be candidates for immediate surgical intervention. Level of Evidence: 3. Abstract : This prospective cohort study investigated the risk factors associated with falls in 135 patients. Lower potassium levels and weaker hand grip strength were independent preoperative predictors for falls in DCM patients.